Leading Determinants for Sustainability of SMEs’ in Bangladesh: Multiple Cases Studies - Tarnima Warda Andalib; Noor Azlinna Azizan; Hasliza Abdul-Halim (International Journal of Supply Chain Management, 2020)
This paper aims to find the leading determinants of SMEs’ of Bangladesh that can create sustainability and long term success for the organizations. In this paper, fifty (50) scholarly articles have been reviewed and ‘qualitative content analysis’ and ‘thematic analysis’ have taken place based on ontological and methodological paradigm approach with multiple case studies. Meanwhile, three cases have been analyzed where the participants’ gave in-depth interview about their SMEs’ and distinct leading determinants.